Fenomena Majelis Zikir (Kajian Pranata Sosial Peribadatan dalam Kehidupan Komunitas Muslim) - Syarial Dedi (UIN Antasari Banjarmasin, 2022)
This paper aims to describe the phenomenon of the proliferation of zikir assemblies in the urban and rural communities, with various motives for their emergence and what benefits are generated by their existence. This phenomenon is fascinating to convey because there is a link between the spiritual and social dimensions. Mistakes in understanding will have fatal consequences for the people themselves. This study uses a normative and descriptive social approach, concluding that the zikir assembly phenomenon began to grow in the reform era around the 1990s. The zikir activities involve many people as Zikir Akbar, Zikir Nasional, Istighosah, Yasinan, Tahlilan, Mujahadahan. The motives for various activities include getting out of a crisis, calamities praying, treatment goals, facing a national exam, just routine activities, celebrations, salvation, thanksgiving or prayer for the soul, even as a mass rally to support specific candidates. The existence of the zikir assembly has many benefits, both from the spiritual aspect and the social aspect. Finally, it can be said that a zikir assembly is a place where the people need to grow and cultivate a sense of diversity.